2017
DOI: 10.4037/ccn2017508
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout Syndrome in Emergency Nurses: A Meta-Analysis

Abstract: Objective To determine the prevalence of burnout (based on the Maslach Burnout Inventory on the 3 dimensions of high Emotional Exhaustion, high Depersonalization, and low Personal Accomplishment) among emergency nurses. Method A search of the terms "emergency AND nurs* AND burnout" was conducted using the following databases: CINAHL, Cochrane, CUIDEN, IBECS, LILACS, PubMed, ProQuest, PsycINFO, SciELO, and Scopus. Results Thirteen studies were included for the Maslach Burnout Inventory subscales of Emotional Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
194
5
19

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(230 citation statements)
references
References 47 publications
12
194
5
19
Order By: Relevance
“…Meta-analytical studies of the prevalence of burnout among A&E nurses have reported values similar to our own for EE and low PA, with prevalence rates of 31% and 29%, respectively. However, these previous papers measured a much higher presence of DP (36%) than in our sample of primary care nurses [24]. On the other hand, a meta-analysis focusing on burnout among oncology nurses observed higher levels of EE, lower levels of DP and PA, than in the primary care nurses in our sample [25].…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Meta-analytical studies of the prevalence of burnout among A&E nurses have reported values similar to our own for EE and low PA, with prevalence rates of 31% and 29%, respectively. However, these previous papers measured a much higher presence of DP (36%) than in our sample of primary care nurses [24]. On the other hand, a meta-analysis focusing on burnout among oncology nurses observed higher levels of EE, lower levels of DP and PA, than in the primary care nurses in our sample [25].…”
Section: Discussioncontrasting
confidence: 77%
“…The number of studies included in the present meta-analysis is lower than in those with A&E nurses [24] or oncology nurses [25]. Meta-analytical studies of the prevalence of burnout among A&E nurses have reported values similar to our own for EE and low PA, with prevalence rates of 31% and 29%, respectively.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The lack of information about risk factors for burnout among nurses working in a particular unit, and about the prevalence of the syndrome, has been addressed in meta‐analytic studies and/or systematic reviews in various health services, including accident and emergency (Gómez‐Urquiza et al ), oncology (Cañadas‐De la Fuente et al ), and paediatrics (Pradas‐Hernández et al ). However, to our knowledge, no such studies or reviews have been conducted regarding the prevalence of burnout among mental health nurses and the risk factors for its development.…”
Section: Introductionmentioning
confidence: 99%
“…As showed in some studies, the prevalence of emotional exhaustion is around 30% in oncology and emergency nurses, while depersonalization prevalence is 15% in oncology nursing or 36% in emergency nursing [16,17]. …”
Section: Introductionmentioning
confidence: 99%